From Craving to Convenience: Factors Influencing Customer Online Purchase Decisions in Lazada Malaysia - Odebunmi Abayomi Tunde; Brahmmanand Sharma; Xue Er Liew; Jia Suen Lew; Wen Jing Li; Lun Kai Liang; Aisha Gupta; Mohini Singh Bhadouria; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Online shopping has become part of everyday life, and understanding what drives people to buy online is more important than ever. This study explores the factors that influence customer purchase decisions on Lazada Malaysia, focusing on convenience, price perception, trust, and website quality. The data obtained were analyzed using descriptive statistics and regression analysis in SPSS to test the proposed hypotheses. The findings show that trust, fair pricing, and high website quality substantially enhance purchase intention. Convenience, although relevant, is now perceived as a basic requirement in online shopping. The study concludes that Lazada can strengthen customer loyalty by improving platform usability, ensuring secure transactions, and offering genuine value. These insights can help e-commerce platforms create more meaningful, trustworthy, and satisfying online shopping experiences.